The Influence of Social Media (Tiktok) in The Environment of PPKN Semester 3 Majors in the Application of Social Justice Values Case Study: Sisingamangaraja University XII North Tapanuli - Silalahi, Meslin; Marbun, Talenta; Purba, Novridah Reanti (Education Achievement: Journal of Science and Research, 2024)
The background of this research is how TikTok use influences social justice by analyzing how users understand and apply social values through the content they share and the content they watch. The research method involves qualitative analysis of TikTok content related to social justice, observation of user interactions, and interviews with a class of 22 UNITA 3rd semester students. The results of this study are that TikTok is very influential on the value of social justice. This depends on how students use it because TikTok has negative and positive impacts. TikTok's impact on social justice values depends on how to use the platform and how TikTok itself works.